ANALISIS POTENSI BAHAYA PADA PEKERJA MENGGUNAKAN METODE HIARO (HAZARD IDENTIFICATION ASSESMENT OF RISK AND OPPORTUNITIES) DI PT XYZ - Darmawan, Yoga (Program Studi Kesehatan dan Keselamatan Kerja, 2020)
PT. XYZ is one of the companies engaged in the palm oil processing industry which often experiences high occupational accident caused by an inadequate K3 management system (SMK3), this case if left unchecked can be detrimental to the company decreased productivity as well as material losses. Costs that must be incurred by the company for each work accident case that occurs are quite large, namely RP. 59.555.539.00 in 2018. By looking at potential hazard and handling work accidents that have not been going well, this company requires hazard identification assessment of risk and Opportunities (HIARO) is one of the latest methods based on ISO 45001. The concept of HIARO takes into account the management of work, social factors (including workload, work hours) leadership, culture in the organization. The result of the study using the HIARO method of the sterilizer station after data processing for January-December 2018 total accident of 34 cases, for a total Frequency Rate value of 1167,56, for the value of Severity Rate of losses workdays of 26 days in 2018, for a total Severity Rate of 0,94. For Boiler station the total accident is 32 case, for a total Frequency Rate value of 995,86, for the value of Severity Rate of lost workdays is 42 days in 2018, for a total Severity Rate of 1,5. This figure shows that K3 Management is not good, so the writer gives a proposal that is to provide special PPE for Sterilizer and Boiler stations such as, Earplug, Handy Talkie, Heat Resistant Glove, Coverall Nomex, Doing Five Minute For Safety.